Measuring Total Factor Productivity of Kenana Sugar Company Plant, (2000-2007) - Mustafa, Lubna M; Bushara, Mohamed O; Ibrahim, Hassan H (Gezira Journal of Economic and Social Sciences; Vol 3 No 1&2 (2012), 2012)
This paper reports the measurement of Total Factor Productivity Change (TFPCH) for Kenana sugar company plant: An empirical analysis with reference to Kenana Sugar Company, based on Data Envelopment Analysis Program (DEAP) using model of input–oriented Malmquist indices Total Factor Productivity(TFP) was carried out. This model could give meaningful results regarding technological and economic behavior relationship over time using time series data of Kenana sugar company plant. Relevant annual data were collected and analyzed to meet the stated objectives. This paper was aimed to measure TFPCH into two components Technological Change (TECH) and Technical Efficiency Change (EFCH) and the latter was further divided into Scale Efficiency Change (SEFCH) and Pure Efficiency Change (PEFCH). The methodology allowed the recovery of various efficiency and productivity measures. The paper was mainly to answer the questions related to technical efficiency, scale efficiency and productivity changes. In the study on Kenana sugarcane plant, the innovation was improving up and down of TECH over time. Scale efficiency operating in Kenana is remained constant return to scale, and  total factor productivity  was improving at  an average of (6.3%) due to improvement in technical change at (6.3%), and improvement in efficiency change, while the average of total factor productivity is deteriorate at (-1.2%) due to deterioration of technical change at an average of (-1.2%) and improvement in efficiency change. The scale efficiency for Kenana Sugar Company is constant return to scale. The study recommended that the policy maker in the Kenana Sugar Company should make effort to benefit from added value of Sugar industry through downstream processes of Sugarcane by product such as molasses bagasse and filter cake, which could be utilized usefully for animal feed, energy  for production and ethanol.